Special issue thinking and rethinking intellectual property - Sarat, Austin (Studies in law, politics, and society ;, 2015)
This special issue of Studies in law, politics, and society focuses on the issue of copyright. The papers contain critical analysis and investigation into existing copyright law and provide insight for policymakers and commentators. The papers contain a range of analyses on issues of copyright. Highlights of the volume include the an examination of three difference aspects of the 1976 Copyright Act, focusing on fair use, statutory damage and formalities; an interesting analysis of the distinction between authentic and "A<U+0303>?A<U+0302>?inauthentic" drawing on the examples of authenticated artwork and counterfeit luxury goods; and an everyday narrative of copyright by examining the laymen understanding of the term, based on comments sections of websites where users post their reactions to copyrightrelated stories.